RETURN ON EQUITY EFFECT AND DEBT TO EQUITY RATIO ON RETURN STOCK OF FOOD AND BEVERAGE - Kristian Chandra (Universitas Trisakti, 2016)
The objective of research is to analyze the influence of Return on Equity and Debt to equity to stock returns. In this study the subjects taken were stocks that entered the food and beverage sector that were listed on the Indonesia Stock Exchange (IDX) during 2010 - 2015. The selection of samples in this study was conducted by Purposive Sampling in order to obtain a representative sample according to predetermined criteria. The number of food and beverage industry samples that meet the criteria are 13 listed on the Indonesia Stock Exchange in 2010-2015. The data analysis technique used to solve the problem in this study is panel data regression analysis with the help of the EViews program. The results of this study indicate that ROE has a positive and not significant effect on stock returns and DER has a positive and significant effect on food and beverage stock returns listed on the IDX in 2010-2015.